Principal Leadership Management in Teacher Development at 010 Laboy Jaya State Elementary School, Bangkinang District, Kampar Regency - Basuki, Basuki; Saam, Zulfan; Syahza, Almasdi (FKIP - Universitas Riau, 2022)
This study aims to analyze the leadership management applied by the Principal of the 010 Laboy Jaya State Elementary School in teacher development, the inhibiting factors in the implementation of the leadership management of the 010 Laboy Jaya State Elementary School Principal in the development of teachers, and the solutions adoptedin overcoming the problems encountered.This study uses a qualitative method with a descriptive approach. Techniques and procedures for data collection in this study through interviews, observation, and documentation. Data analysis techniques with qualitative methods are the data reduction stage, data presentation, conclusion drawing and verification stages. .Based on the results of the study, it can be concluded that (1) the leadership management applied by the Principal of the 010 Laboy Jaya Elementary School in teacher development is good, it can be seen from the planning, organizing, implementation, evaluation, and follow-up aspects. (2) The inhibiting factors or obstacles faced are the lack of experience of teachers, both experience in learning and experience in school organizations, Lack of experience in communication techniques, and There are still many activities of teachers outside the task of the learning process. (3) The solution to the obstacles faced is to carry out education and training, KKG, seminars, give assignments such as special pickets, carry out self-development activities.